Increasing age at radical prostatectomy: a total population analysis in Germany from 2006 to 2022 - Baunacke, Martin; Huber, Johannes; Haak, Lennard; Thomas, Christian; Groeben, Christer (Annals of surgical oncology, 2026)
With increasing life expectancy, the number of elderly patients seeking curative treatment for prostate cancer is rising. Radical prostatectomy (RP), particularly the robotic approach, has proven feasible in older men. This study analyzes trends in RP among men aged ≥ 75 years of age in Germany between 2006 and 2022.